A Gauntlet in the Wilderness, or Multifaceted Transcultural Crossings in Mary Rowlandson’s Narrative (1682) - Tarnóc, András (FOCUS: Papers in English Literary and Cultural Studies, 2006)
By the end of the seventeenth century the New England wilderness achieved a special historical significance as a site of intercultural exchange, during which the encounter between Anglo settlers and Indians contributed to the mutual shaping of both civilizations. As King Philip’s War (1675-1676) set most of New England aflame more and more settler communities were victimized by Indian attacks and being forced into captivity became a characteristic experience of several English families dwelling on the intercultural borderline. Following the attack on Lancaster on February 10, 1676 Mary White Rowlandson was forcibly carried away by Narragansett Indians. As a result of the assault and the following capture she lost several members of her family, was tom from her husband and children and she was compelled to undergo a forced march in the wilderness.